2016
DOI: 10.1007/s00167-016-4272-1
|View full text |Cite
|
Sign up to set email alerts
|

Origin and insertion of the medial patellofemoral ligament: a systematic review of anatomy

Abstract: PurposeThe medial patellofemoral ligament (MPFL) is the major medial soft-tissue stabiliser of the patella, originating from the medial femoral condyle and inserting onto the medial patella. The exact position reported in the literature varies. Understanding the true anatomical origin and insertion of the MPFL is critical to successful reconstruction. The purpose of this systematic review was to determine these locations.MethodsA systematic search of published (AMED, CINAHL, MEDLINE, EMBASE, PubMed and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 108 publications
4
74
1
2
Order By: Relevance
“…Native MPFL properties also serve to represent a true “restorative” procedure by restoring the properties of the MPFL to its pre‐injury state. The MPFL femoral insertion area covers a triangular space between the adductor tubercle, medial femoral epicondyle and gastrocnemius tubercle .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Native MPFL properties also serve to represent a true “restorative” procedure by restoring the properties of the MPFL to its pre‐injury state. The MPFL femoral insertion area covers a triangular space between the adductor tubercle, medial femoral epicondyle and gastrocnemius tubercle .…”
Section: Methodsmentioning
confidence: 99%
“…The MPFL femoral insertion area covers a triangular space between the adductor tubercle, medial femoral epicondyle and gastrocnemius tubercle. 42 As a non-anatomical reconstruction of the MPFL can lead to non-physiological PF loads and kinematics, the MPFL femoral insertion anatomy chosen was within the boundary of the medial epicondyle. 43 The MPFL was initially tensioned such that the tension was minimal across passive flexion from 5°to 70°.…”
Section: Virtual Surgical Interventionmentioning
confidence: 99%
“…Previously, it was widely accepted that the lateral portion of the MPFL had a broad attachment onto the proximal medial portion of the patella over a 20-to 30-mm-wide area. 20 However, a recent cadaveric study of 28 knees by Tanaka 21 found that MPFL insertion onto the patellar demonstrated considerable variability. In the 28 knees that were analyzed, the mean percentage of MPFL fibers that inserted onto the patella was 57.3 AE 19.5% (range: 0-100%; 95% confidence interval [CI]: 50.1-64.5).…”
Section: Anatomy and Biomechanicsmentioning
confidence: 99%
“…2). 6,7) Manual reduction was tried when the patient was awake. The patella reduced but dislocated immediately following reduction.…”
Section: Casementioning
confidence: 99%